Smoker’s melanosis: Isolated pigmented lesion in the laryngopharynx and esophagus - Changela, Kinesh; Reddy, Madhavi (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Changela K, Reddy M. Smoker’s melanosis: isolated pigmented lesion in the laryngopharynx and esophagus. Turk J Gastroenterol 2017; 28: 524-5.